The hormonal profile of benign breast disease - Samoli, E (Nature Publishing Group, 2013)
BACKGROUND: Limited information exists about the endocrine milieu of benign breast disease (BBD), a documented breast cancer risk factor. We compared blood levels of estrogens, testosterone and insulin-like growth factor-1 (IGF-1) between BBD patients by histological type and women without breast pathology. METHODS: We studied 578 BBD patients and 178 healthy women in Athens, Greece, who provided blood samples, and completed interviewer-administered questionnaires. RESULTS: Of the BBD patients, 254 had non-proliferative disease, 268 proliferative disease without atypia and 56 atypical hyperplasia. Comparing BBD patients with healthy women, the per cent differences (and 95% confidence intervals) for blood hormones, among pre-menopausal and peri/post-menopausal women, respectively, were: 22.4% (−4.0%, 56.1%) and 32.0% (5.6%, 65.1%) for estradiol; 26.2% (10.1%, 44.8%) and 30.9% (16.8%, 46.6%) for estrone; 19.5% (3.1%, 38.4%) and 16.5% (−5.0%, 42.9%) for testosterone; and −5.2% (−13.8%, 4.4%) and −12.1% (−19.8%, −3.6%) for IGF-1. Steroid hormones tended to be higher in proliferative compared with non-proliferative BBD. CONCLUSIONS: Circulating steroid hormones tend to be higher among women with BBD than women with no breast pathology and higher in proliferative than non-proliferative disease; these patterns are more evident among peri/post-menopausal women. In peri/post-menopausal women IGF-1 was lower among women with BBD compared with healthy women.